Jesus and the Gospel movement : not afraid to be partners - Thompson-Uberuaga, William, 1943- (Eric Voegelin Institute series in political philosophy., 2006)
"Thompson-Uberuaga reconsiders the image of Jesus Christ by examining his relationships with others and the bonds he formed as the gospel movement took shape around him. He engages the works of Voegelin, Gadamer, and others to explore fully the political dimensions of the emerging church. Includes Internet links for supplementation"--Provided by publisher